2009
DOI: 10.1002/cncr.24157
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 gene polymorphisms reduce the risk of oral premalignant lesions

Abstract: BACKGROUND: Oral premalignant lesions (OPLs) have the potential to transform into malignant oral cancers. Overexpression of the cyclooxygenase‐2 gene (COX‐2) is observed frequently in OPLs and oral cancers, suggesting that this gene may play an important role in the progression of oral cancer. Single‐nucleotide polymorphisms of COX‐2 have been associated with the risk of multiple cancers; however, to date, their effects on OPL susceptibility have not been evaluated sufficiently. METHODS: The authors conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
4
14
0
1
Order By: Relevance
“…We observed higher COX-2 activity in SCC patients with ¡765GG genotype (2.17 § 1.6 U/mg protein) versus BCC patients with the same genotype (1.91 § 1.12 U/mg protein) that sustains no link between genotype and tumor type. Intra-group comparison showed an intra-group variation in BCC patients with signiWcant lower COX-2 activity in C-allele carriers compared to non-carriers (t test, p < 0.001), and also in SCC patients (allele C carriers vs. non-carriers, t test, p < 0.0001) which is similar to other Wndings regarding signiWcantly lower COX-2 activity in C-allele carriers [35,36]. On this basis, our results suggest that COX-2 activity might be a contributing factor to nonmelanoma skin cancer, but these Wndings reXect diVerences in unidentiWed characteristics other than PTGS2 G>C polymorphism.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We observed higher COX-2 activity in SCC patients with ¡765GG genotype (2.17 § 1.6 U/mg protein) versus BCC patients with the same genotype (1.91 § 1.12 U/mg protein) that sustains no link between genotype and tumor type. Intra-group comparison showed an intra-group variation in BCC patients with signiWcant lower COX-2 activity in C-allele carriers compared to non-carriers (t test, p < 0.001), and also in SCC patients (allele C carriers vs. non-carriers, t test, p < 0.0001) which is similar to other Wndings regarding signiWcantly lower COX-2 activity in C-allele carriers [35,36]. On this basis, our results suggest that COX-2 activity might be a contributing factor to nonmelanoma skin cancer, but these Wndings reXect diVerences in unidentiWed characteristics other than PTGS2 G>C polymorphism.…”
Section: Discussionsupporting
confidence: 87%
“…These Wndings are in line with prior evidence regarding signiWcant lower COX-2 activity in C-allele carriers [35,36]. We found a signiWcant variation in COX-2 activity between BCC and SCC patients (p = 0.0019).…”
Section: Correlation Of Ptgs2 Polymorphism With Cox-2 Activity In Bccsupporting
confidence: 92%
“…CC genotype of this SNP was associated with an unfavorable distant DFS (DDFS) of EBC. A few previous studies also demonstrated that this genotype was significantly associated with the risk of Korean and Chinese lung adenocarcinomas (Hu et al 2005;Park et al 2006), bladder cancer (Yang et al 2008), and oral premalignant lesions adjusted for ethnicity (Pu et al 2009). However, further study is warranted to define the significance of this polymorphism in breast cancer due to the lack of statistical correlations with DFS and OS in the current study.…”
Section: Discussionmentioning
confidence: 89%
“…There are reported significant associations with basal cell, bladder, breast, colorectal, gastric, lung, prostate and ovarian cancers. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Across cancer tissues of different origin, each allele paradoxically has been associated with increased risk of cancer. However, if studies are stratified by cancer type, there is greater consistency in the assignment of the risk allele.…”
mentioning
confidence: 99%
“…29 Other biological factors such as gender and age and environmental factors such as non-steroidal antiinflammatory drug use and smoking status also influence the strength of association with cancer incidence. 15,25,27,28,30,31 Considered together, the prevailing evidence suggests that rs5275 is associated with cancer incidence, but the associations are complex.…”
mentioning
confidence: 99%